Work posture analysis and complaint risk using Nordic Body Map (NBM) and Rapid Entire Body Assessment (REBA) methods - Umyati, Ani; Mariawati, Ade Sri; Peti, Peti (Journal Industrial Servicess, 2023)
This research investigates work posture analysis and complaint risks associated with polyethylene pellets production at a petrochemical company in Cilegon, Indonesia. The concerns center on improper work postures among forklift operators engaged in repetitive tasks and loading personnel involved in manual handling, such as transferring bagged pellets onto trucks. The study aimed to identify the Nordic Body Map (NBM) questionnaire's primary complaint categories, assess the Rapid Entire Body Assessment (REBA) score, determine recommended weights for workers using Recommended Weight Limit (RWL) and lifting Index (LI) calculations, and propose enhancements to mitigate the risk of MSDs. According to the NBM questionnaire, both forklift operators and loading personnel reported experiencing moderate to high levels of Musculoskeletal Disorders (MSD) discomfort. REBA scores revealed forklift operators scoring between 5 and 6, while loading dock workers scored between 11 and 12. The estimated RWL for loading personnel in different positions is 6.531 kg, 3.5707 kg, and 6.0463 kg, respectively. Recommendations include improving the work system, conducting health assessments, revising hiring criteria, developing adjustable tables, optimizing packaging bags, establishing SOPs, and modifying forklift area components. These suggestions remain broad, with detailed plans intended for future research and implementation.